Coupling Pulse Radiolysis with Nanosecond Time-Resolved Step-Scan Fourier Transform Infrared Spectroscopy: Broadband Mid-Infrared Detection of Radiolytically Generated Transients. Issue 9 (September 2022) - Grills, David C.; Layne, Bobby H.; Wishart, James F.
We describe the first implementation of broadband, nanosecond time-resolved step-scan Fourier transform infrared (S 2 -FT-IR) spectroscopy at a pulse radiolysis facility. This new technique allows the rapid acquisition of nano- to microsecond time-resolved infrared (TRIR) spectra of transient species generated by pulse radiolysis of liquid samples at a pulsed electron accelerator. Wide regions of the mid-infrared can be probed in a single experiment, which often takes < 20–30 min to complete. It is therefore a powerful method for rapidly locating the IR absorptions of short-lived, radiation-induced species in solution, and for directly monitoring their subsequent reactions. Time-resolved step-scan FT-IR detection for pulse radiolysis thus complements our existing narrowband quantum cascade laser-based pulse radiolysis-TRIR detection system, which is more suitable for acquiring single-shot kinetics and narrowband TRIR spectra on small-volume samples and in strongly absorbing solvents, such as water. We have demonstrated the application of time-resolved step-scan FT-IR spectroscopy to pulse radiolysis by probing the metal carbonyl and organic carbonyl vibrations of the one-electron-reduced forms of two Re-based CO2 reduction catalysts in acetonitrile solution. Transient IR absorption bands with amplitudes on the order of 1 × 10 −3 are easily detected on the sub-microsecond timescale using electron pulses as short as 250 ns. Graphical Abstract